Macroeconomic Indicators and Regional Government Capital Expenditure: Panel Data Analysis of Provinces in Sumatra 2019–2024 - Merri Anitasari; Zoniarti Zoniarti (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study analyses the effects of economic growth, inflation, interest rates, unemployment rates, and poverty rates on local government capital expenditures in 10 provinces in Sumatra during the 2019–2024 period. Using a panel data regression approach with fixed and random effects models and the Hausman test, we found that economic growth had a significant positive effect on capital expenditures, while inflation and poverty rates had a significant negative effect. These results emphasize the importance of macroeconomic stability and fiscal capacity in encouraging public investment at the regional level.